1996
DOI: 10.1149/1.1836407
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Fine‐Grain Yttrium‐Based Phosphors by Sol‐Gel Process

Abstract: The preparation, characterization, and luminescence of yttrium-based phosphors such as europium activated yttrium oxide (red) and terbium activated yttrium aluminate (green) by sol-gel processes is presented. The sols of yttrium hydroxide were synthesized by various routes. It was found that the sols obtained through an ion exchange column were pure and without any cross contamination. The aluminum hydroxide sols were prepared from aluminum chloride and ammonium hydroxide. A number of gel samples were synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(145 citation statements)
references
References 1 publication
(1 reference statement)
2
142
0
1
Order By: Relevance
“…Un ejemplo de ello es su aplicación en el campo de la óptica y el tradicional desarrollo de láseres y fósforos en esta estructura (11,12,13,14).…”
Section: Introductionunclassified
“…Un ejemplo de ello es su aplicación en el campo de la óptica y el tradicional desarrollo de láseres y fósforos en esta estructura (11,12,13,14).…”
Section: Introductionunclassified
“…2. The particles have a narrow size distribution and the median diameter is about 2.3 µm, which elucidates why the phosphors are meeting the production requirements of solid lighting facilities [30]. (CT) [31], the other is a narrow peak region above 362 nm which is assigned to the 4f 7 configuration transitions of Eu 3+ from the ground state to the excited state in the host lattice [32].…”
Section: Analyses Of Xrd and Size Distributionmentioning
confidence: 90%
“…However, by this novel reverse micellar route, we could bring down the temperature required for the formation of single-phase Sr 2 SiO 4 to as low as 600 C. Figure 3 shows the typical SEM image of Sr 1.99 Eu 0.01 SiO 4 phosphor, and it is clearly observed that the particles have a mixed morphology of agglomerated particles with some of them showing rod-like morphology with the diameter of about 100 nm and the length of 0.5-1 mm, which makes the phosphor have high surface area. It is found that the phosphors with higher surface area have better thermal conductivity when excited with highenergy photons [22] and are favourable to the lifetime of ultraviolet GaN-based w-LED. Based on the morphological characterisation, a mechanism is proposed for the formation of Sr 1.99 Eu 0.01 SiO 4 nanorods and can be seen from Figure 4.…”
Section: Instrumentationmentioning
confidence: 99%